One Hundred Thousand, Ended in Misery Five Years - Rahman, Malik Akbar Mulki (Law Research Review Quarterly, 2018)
Indonesia is a country that adheres to a democratic system where every five years organizes a democratic party, the community participation rate from year to year has been shown to increase in 2014 reaching 75.11 percent from 71.7 percent in 2009 which showed an increase of 3.4 percent. Even though the number of people participating in democracy is increasing, there are still problems in organizing elections ranging from abstentions to fraud in the elections by legislative and executive candidates, who are often called upon by the people of money politics or money attacks. To overcome this problem, the author has the idea of ​​forming an independent body, specifically overseeing the election so that there are no violations in the form of money politics, and the most important thing is socialization to the public to work together in making the election successful by providing an understanding of the forms of violations in the election and if you see fraud, report directly to the authorities in this case, the KPU. The purpose of writing this essay is to reduce the level of fraud in elections so that elections can be fair, free, transparent and honest so that people are not disadvantaged tomorrow, because one chooses a leader. The use of research methods using quantitative descriptive methods with sources from journals, KPU, etc. Hopefully this article can be a solution to the election in 2019.